Regioselective synthesis of 3,5-diaryl-4-methylisoxazoles - Lokhande, P.D.; Ali, Hapipah Mohd; Khaledi, H.; Hasanzadeh, K. (2012)
Abstract: A new class of isoxazole derivatives, namely 2-(3-aryl-4-methylisoxazol-5-yl)phenols, has been efficiently synthesized through the regioselective reaction of 2-aryl-3-methylchromones with hydroxylamine. The products were characterized by spectroscopic methods and X-ray crystallography. Graphical Abstract: [Figure not available: see fulltext.]. © 2012 Springer-Verlag.